Karl Marx’s Philosophy and Its Relevance Today - Rashid, Haroon (Philosophy and Progress, 2019)
How do we see the world? What is the way of looking at the world? In other words, how do we explain the problems of our life and the world we live in? This is what philosophy does, i.e., philosophy is a way of explaining life and the world. More precisely, philosophy is an outlook of the fundamental problems of life and the world. A philosopher starts his thinking with the exercise of rationality. He makes a rational investigation of the problems with which he is concerned. In this sense, philosophy is a rational outlook of the fundamental problems of life and the world. A philosopher is a rational and critical thinker and in this way of thinking he formulates his ideas and builds theories about life and the world. In this sense, philosophy is mainly a theoretical activity and a philosopher is concerned with conceptual or theoretical activity. This is the traditional way of defining philosophy. Philosophy and Progress, Vol#61-62-; No#1-2; Jan-Dec 2017 P 15-42